Margin of safety in Value Investing for Sharia Stock Investment from the Perspective of Maqasid Sharia - Muhammad Ismail Alfaruqy; Mukhaer Pakkanna; Supardi Mursalin (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2026)
Purpose: This study aims to conceptually analyze and normatively examine the benefits of margin of safety in value investing techniques in preventing stock speculation, evaluate value investing techniques from the perspective of maqashid sharia, and identify similarities between value investing and maqasid sharia.Design/Methodology: Using a normative-conceptual study using a maqasid sharia based analytical framework, this study was conducted through literature review and secondary data analysis from various relevant references.Findings: The results show that the application of margin of safety in value investing in sharia stocks can increase market stability and reduce speculative practices, in line with the principle of asset protection (hifzh al-maal) in sharia objectives. This strategy has also proven effective in minimizing the elements of gharar and maysir, making it an ethical and responsible investment model.Practical Implications: This enriches the discourse on the integration of sharia principles into modern investment strategies and provides practical implications for investors, regulators, and sharia capital market players to create a more equitable, inclusive, and sustainable investment ecosystem.Originality/Value: This study integrates the value investing approach with the application of margin of safetyinto the maqasid sharia framework as the basis for sharia investment decision-making. This study offers a new approach by positioning value investing not only as a strategy to achieve financial returns, but also as a means to realize justice and economic stability. It also contributes to expanding the discourse on Islamic finance by offering an alternative investment approach that is not only spiritually, socially, and economically responsible, but also based on ethics and sustainability.